Mulheres negras e plurais: gênero, raça e sexualidade em Goyaz, século XIX - Silva, Murilo Borges (2019)
It is possible to verify, along the 19th Century, the production of speeches and practices which were interested in nominating, ranking and hierarchizing the society, producing identities and differences which were shaped to the subjects´ behaviors and bodies. Such process is underlined by the class/social condition, race and gender intersections, which indicates the existence, in this period, of a discursive set concerned about creating and informing the origins, the different human types and their destinations. Considering these identities´production and subject´s building game, we propose, in this study, to investigate how discursive and non-discursive practices, which are legitimized by power relations, historically produced black female bodies, in Goiás, at the 19th Century. Therefore, we focused particurlaly on the examination of speeches which were made by the historiography concerning Goiás: travelers´ works, criminal cases and the Goiás State´s press. From the theoretic point of view, we used studies such as: Foucault (2015), Louro (2011), Lima (2003), Carneiro (2006) and Albuquerque Jr. (2007,2013) whose understandings runs through the idea which the subjects and their identities are built in the culture and History ambits, therefore, they are multiple and distinct, and they vary as they are asked. The argument that we defend is that the process of producing black women, in different discursive materialities, suggests the advances of moral control over a poorer social portion, effectivated, with greater apparatus, from the end the 19th Century and beginning the 20th Century, but drafted well before that, in the narratives of European travelers and in judicial and police proceedings, for example. The idea was in controlling, subaltering, discriminating, disciplining and punishing behaviors and values incompatible with moral, sexual and even amorous norms. The purpose of such vigilance was in the construction a disciplinary and economic society, focusing heavily on women and children, with the aim of making them docile, useful and orderly.